Contribution to the etio-pathogenesis. Histopathology and treatment of schizophrenia - Palma, Eduardo C; Rodríguez Juanotena, Jorge; Sotelo, J Roberto; Polero, Héctor; Taibo, Walter; Perillo, Walter (Cirugía del Uruguay, 2020)
Presented at session 20th December 1956